Social media for political information: a systematic literature review - Tan, Jue Jun; Amira Firdaus,; Iffat Ali Aksar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social media exerts a considerable influence on the democratic process in the modern digital age. Meanwhile, political information appears to be a precious commodity in the political process and functioning democracy. Despite the proliferation and globalization of research in these areas, lesser efforts have been made to systematically review and integrate discoveries from previous studies to assess the current state of research on social media use for political information. This article aims to systematically collect, condense, analyze and report the holistic, empirical findings from extant literature between 2010 and 2020 to offer a rich overview of research on social media use for political information. The Systematic Literature Review (SLR) integrated both the automatic and manual search strategies for data collection. Out of the 292 papers, 23 primary studies were identified to answer a defined set of research questions. Political communication and political participation were the two most popular themes. Uses and gratifications theory appeared to be the most used theory. Scholars are keen to explore the indirect variables that exist at any stage in between the process of consuming political information on social media and political participation. The review results suggested that although social media is widely used for political information, exploration on the body of knowledge of this domain is not receiving much attention and is reported roughly. An explicit analytical discussion on the review results with identified knowledge gaps that call for further exploration and conclusion is offered.